PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN MEMBELIAN PRODUK WARDAH - S, Niantoro (Universitas YPPI Rembang, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions. This research was conducted in the wholesale center of Cikarang, with the population being consumers of Wardah Foundation products. The dependent variable is the purchase decision, while the independent variables are product quality and price. With the sampling technique as many as 134 respondents. The data collection technique in this study was carried out by distributing a questionnaire (questionnaire) which was statistically processed with the help of SPSS 20.0 and using multiple linear regression analysis. The results of the descriptive analysis show that the product quality is included in the high category, and the price is also included in the high category. The results of the partial test (t-test) show that product quality has a negative and insignificant effect on purchasing decisions, and price has a positive and significant effect on purchasing decisions. And the results of the simultaneous test (F-test) show that product quality and price together have a positive and significant effect on purchasing decisions. Keywords: Product Quality, Price and Purchase Decision